EFFECT OF TESTOSTERONE DEPRIVATION ON SMOOTH MUSCLE COLLAGEN RATIO IN BLADDER WALL OF WISTAR RATS - Rachman, Wendi (Indonesian Journal of Urology, 2011)
Objective : To evaluate the smooth muscle-collagen fibers ratio in the bladder wall of castrated male wistar rats. Material & Method : Sixteen wistar rats were equally assigned to castrated group (n=8) and sham group (n=8). All wistar rats were subjected to a one-week acclimatization period before undergoing treatment. After 60 days, cystectomy was performed in all rats in both groups and subsequent specimens of the bladder were taken to semi quantitative pathology analysis using haematoxylineosin (HE) staining under Olympus CX20 microscope by a uropathologist. Results were then grouped into parametric data and analyzed using independent T-test. Results: Smooth muscle fibers were significantly lower in the castrated group 0,615±0,13 (p=0,01). There was higher amount of collagen fibers in the castrated group 0,385±0,18 (p=0,04). Smooth muscle to collagen ratio in the castrated group was also significantly lower compared to the control group 1,597±0,25 (p=0,03). Conclusion : Testosterone deprivation significantly reduces the smooth muscleand smooth muscle to collagen fibers ratio in bladder wall of castrated rats.